An Unusual Case of Cannula Obstruction Resulting from Venous Thromboembolism - Ozdirik, Jessica E. (J Extra Corpor Technol, 2014)
Cerebral strokes of unknown origin frequently present with a patent foramen ovale (PFO), a common atrial septal defect occurring in approximately 25% of the adult population. Deep vein thrombosis (DVT) or pulmonary embolism (PE) in the presence of a PFO can produce paradoxical systemic embolization subsequent to an increase in pulmonary pressure, permitting entry of thrombi into the arterial circulation. Diagnosis of an impending paradoxical embolism (IPDE) involves the detection of DVT or PE in the presence of an abnormal communication between left and right circulations and may include a right-to-left shunt. Treatment includes oral anticoagulation, antiplatelet agents, thrombolysis, transcatheter closure of the defect, or surgical embolectomy and PFO closure. As a result of risks of intracranial hemorrhage with fibrinolysis, pulmonary embolectomy using cardiopulmonary bypass (CPB) and deep hypothermia is a primary treatment with a surgical mortality rate at approximately 5%. Despite optimal management, IPDE is associated with a mortality rate of 18%. Prompt diagnosis and treatment is critical in avoiding systemic thromboembolization and strokes in these patients. We report a case of superior vena cava cannula obstruction resulting from a paradoxical embolus traversing a PFO during surgery. Warning signs and management during CPB are discussed.